Development of Molecular Anisotropy in Centrifugally Spun Fibers as Compared to Electrospun Fibers. Issue 11 (31st August 2016) - Mohan, Saeed D.; Mitchell, Geoffrey R.; Davis, Fred J.
Abstract : The molecular anisotropy that is developed in microscale, centrifugally spun atactic‐polystyrene fibers prepared from the solution state is examined and comparisons are made to electrospun fibers. Utilizing small angle neutron scattering, a ratio of the radius of gyration parallel to‐/perpendicular to‐ the fiber axis is measured and a model of chain anisotropy development in the centrifugal spinning process is described. Abstract : The molecular anisotropy that is developed in microscale, centrifugally spun atactic‐polystyrene fibers prepared from the solution state is examined. Small angle neutron scattering is utilised to examine the molecular orientation of the polymer chain conformation in centrifugally spun fiber samples and comparisons are made to anisotropy developed in electrospun fiber samples. The average values of molecular anisotropy developed in the centrifugally spun fibers measured a ratio of the radius of gyration parallel to‐/perpendicular to‐ the fiber axis as 1.02, lower than the average of 1.05 observed for the electrospinning process. The highest level of anisotropy observed for the centrifugally spun fiber samples is ≈1.04, compared with a value of 1.063 for electrospinning. A model of chain anisotropy development in the centrifugal spinning process relating to the tangential speed and solvent evaporation is described.